Document Management System - Jain, Deepak (Indian Journal of Computer Science, 2021)
Record keeping has been done since time immemorial. As processes became complex, the number of documents created increased, and as technology evolved paper documents were replaced with digital documents. It became necessary to have systems that could make it easy for users to store and search documents. Document Management Systems (DMS) were developed to satisfy these requirements. This paper describes a typical DMS, its features, architecture, uses, and new technologies.